2016
DOI: 10.1063/1.4972285
|View full text |Cite
|
Sign up to set email alerts
|

Power enhancement of partially shaded PV arrays through shade dispersion using magic square configuration

Abstract: This paper proposes a new static reconfiguration technique to configure the modules in the Photo-Voltaic (PV) array so as to enhance the generated power from the array under partial shading conditions. In this approach, the physical location of the modules in a Total Cross Tied (TCT) connected PV array is arranged based on the Magic Square (MS) pattern so as to distribute the shading effect over the entire array. Further, this arrangement of modules is done without altering the electrical connection of the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The obtained results for the TCT and MS puzzle configuration are compared and it is observed that the MS puzzle configuration has maximum FF, power, and voltage at GMPP of 960W with reduced power losses. The authors in [113], implemented an experimental PV array system of 3×3 and 6×6 sizes for SP, BL, TCT, and MS puzzle configurations under the predefined partial shading patterns. Where the performance of MS puzzle configuration is found best and acquires the maximum voltage at GMPP of 2.88W with a varying range of irradiation level 200-900W/m 2 .…”
Section: (E) Magic Square Configurationmentioning
confidence: 99%
“…The obtained results for the TCT and MS puzzle configuration are compared and it is observed that the MS puzzle configuration has maximum FF, power, and voltage at GMPP of 960W with reduced power losses. The authors in [113], implemented an experimental PV array system of 3×3 and 6×6 sizes for SP, BL, TCT, and MS puzzle configurations under the predefined partial shading patterns. Where the performance of MS puzzle configuration is found best and acquires the maximum voltage at GMPP of 2.88W with a varying range of irradiation level 200-900W/m 2 .…”
Section: (E) Magic Square Configurationmentioning
confidence: 99%
“…In this type of configuration, the idea of distributing the shaded area over the entire region of solar array have taken into consideration. The location of solar cells/modules with TCT configuration is replaced according to magic square [8].…”
Section: F Magic Square Configurationmentioning
confidence: 99%
“…Later, B. Indu Rani proposed a technique based on physical location, which exploits the Sudoku logic in a TCT configured solar array [7]. In a similar manner magic square based logic is also proposed to minimize the effect of shading on solar array [8]. Many authors have attempted to compare the performance of SP, BL and TCT reconfiguration techniques with and without bypass diode through simulations and experimentation [9]- [14].…”
Section: Introductionmentioning
confidence: 99%
“…11 A considerable effort was made on magic square patterns where the physical locations of the panels were changed without changing the electrical connections. 12,13 A modified magic square pattern and modified hybrid configurations were proposed along with progressive shading patterns. 14 In order to disperse the effect of shading for minimising both the line losses and mismatch losses, a 3 × 3 array and 7 × 7 array with bypass diodes was proposed.…”
Section: Introductionmentioning
confidence: 99%